Comparative immunogenicity and efficacy of equivalent outer membrane vesicle and glycoconjugate vaccines against nontyphoidal Salmonella - Micoli, F; Rondini, S; Alfini, R; Lanzilao, L; Necchi, F; Negrea, A; Rossi, O; Brandt, C; Clare, S; Mastroeni, P; Rappuoli, R; Saul, A; et al. (National Academy of Sciences, 2018)
Nontyphoidal Salmonellae cause a devastating burden of invasive disease in sub-Saharan Africa with high levels of antimicrobial resistance. Vaccination has potential for a major global health impact, but no licensed vaccine is available. The lack of commercial incentive makes simple, affordable technologies the preferred route for vaccine development. Here we compare equivalent Generalized Modules for Membrane Antigens (GMMA) outer membrane vesicles and O-antigen-CRM197 glycoconjugates to deliver lipopolysaccharide O-antigen in bivalent Salmonella Typhimurium and Enteritidis vaccines. Salmonella strains were chosen and tolR deleted to induce GMMA production. O-antigens were extracted from wild-type bacteria and conjugated to CRM197 Purified GMMA and glycoconjugates were characterized and tested in mice for immunogenicity and ability to reduce Salmonella infection. GMMA and glycoconjugate O-antigen had similar structural characteristics, O-acetylation, and glucosylation levels. Immunization with GMMA induced higher anti-O-antigen IgG than glycoconjugate administered without Alhydrogel adjuvant. With Alhydrogel, antibody levels were similar. GMMA induced a diverse antibody isotype profile with greater serum bactericidal activity than glycoconjugate, which induced almost exclusively IgG1. Immunization reduced bacterial colonization of mice subsequently infected with Salmonella S Typhimurium numbers were lower in tissues of mice vaccinated with GMMA compared with glycoconjugate. S. Enteritidis burden in the tissues was similar in mice immunized with either vaccine. With favorable immunogenicity, low cost, and ability to induce functional antibodies and reduce bacterial burden, GMMA offer a promising strategy for the development of a nontyphoidal Salmonella vaccine compared with established glycoconjugates. GMMA technology is potentially attractive for development of vaccines against other bacteria of global health significance.